2011
DOI: 10.1021/ef201376w
|View full text |Cite
|
Sign up to set email alerts
|

Heteronuclear Single-Quantum Correlation–Nuclear Magnetic Resonance (HSQC–NMR) Fingerprint Analysis of Pyrolysis Oils

Abstract: The pyrolysis of softwood kraft lignin, cellulose, and Loblolly pine wood was examined at 400, 500, and 600 °C. The analysis of the yields of pyrolysis products indicated that lignin yielded the largest amount of a heavy oil and char and only trace levels of a light oil. In contrast, cellulose produced minor amounts of a heavy oil and char and more light oil. All of the pyrolysis oils were analyzed by heteronuclear single-quantum correlationÀnuclear magnetic resonance (HSQCÀNMR) to analyze the structural compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
93
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 101 publications
(101 citation statements)
references
References 34 publications
8
93
0
Order By: Relevance
“…This is in agreement with the results obtained by Ben and Ragauskas [26], who reported that the bond energy of the C-O bond (CH 3 -O) in the methoxyl groups is lower than the O-H bond in the hydroxyl groups, which shows that the methoxyl groups decompose more easily than the hydroxyl groups.…”
Section: Gc-ms Analysissupporting
confidence: 93%
See 2 more Smart Citations
“…This is in agreement with the results obtained by Ben and Ragauskas [26], who reported that the bond energy of the C-O bond (CH 3 -O) in the methoxyl groups is lower than the O-H bond in the hydroxyl groups, which shows that the methoxyl groups decompose more easily than the hydroxyl groups.…”
Section: Gc-ms Analysissupporting
confidence: 93%
“…5. These were performed based on the 1 H- 13 C NMR assignments of the model lignin-derived compounds in DMSO-d 6 and some references [26,[36][37][38][39][40][41][42]. These crosspeaks are related to the main types of aromatic products confirmed by GC-MS measurement.…”
Section: Gc-ms Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…After the use of Y zeolite, the heavy oils contained 76.4% less methoxyl groups than the blank pyrolysis oil, which indicates a very efficient decomposition of methoxyl groups and this result could explain the increasing contents of catechol type and p-hydroxyphenyl type hydroxyl groups detected by 31 P NMR. The two types of methyl aromatic bonds (methyl-Ar groups with and without a hydroxyl or ether group in the ortho position) in the heavy oils are reported to be the rearrangement products of methoxyl groups [24]. After the use of Y or M zeolites, the heavy oils contained relatively large amount of methyl aromatic bonds, which is the evidence for the enhanced cleavage of methoxyl groups.…”
Section: Quantitative 13 C Nmr Analysis Of Pyrolysis Oilmentioning
confidence: 95%
“…However, the limitations of 13 C NMR can be addressed using modern 2D NMR (such as HSQC-NMR) techniques, which has been developed to semi-quantitatively analyze over 30 different C-H bonds in the pyrolysis oils [24][25][26][27]. We have previously shown that HSQC-NMR was uniquely well suited to analyze various C-H bonds present in the pyrolysis oils.…”
Section: Hsqc-nmr Analysis Of Pyrolysis Oilmentioning
confidence: 99%